2002
DOI: 10.1089/153834402765035626
|View full text |Cite
|
Sign up to set email alerts
|

Primary Culture of Rat Hepatocytes After Cold Storage in the University of Wisconsin Solution: A Tool to Study the Effects of Hypothermic Preservation

Abstract: The effect of long-term hypothermic preservation on the function and morphology of rat hepatocytes cultured up to 120 h was studied. Cold storage was performed using modified University of Wisconsin solution, originally developed for organ preservation. After different times of cold storage of hepatocytes, a primary culture system was used to evaluate their ability to attach and form a monolayer of cells on a Petri dish, as well as to perform metabolic functions: capacity of maintaining intracellular enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Rat hepatocytes were obtained from adult male Sprague-Dawley rats. The hepatocytes were isolated as described previously (25), using the two-step perfusion procedure with 0.025% collagenase Type IV. The viability of the cells was tested using trypan blue exclusion and was always g85%.…”
Section: Methodsmentioning
confidence: 99%
“…Rat hepatocytes were obtained from adult male Sprague-Dawley rats. The hepatocytes were isolated as described previously (25), using the two-step perfusion procedure with 0.025% collagenase Type IV. The viability of the cells was tested using trypan blue exclusion and was always g85%.…”
Section: Methodsmentioning
confidence: 99%
“…Rat hepatocytes were obtained from adult male Sprague–Dawley rats. Isolation was as described previously ( Pazo et al ., 2002 ) by the two‐step perfusion procedure with 0.025% collagenase Type IV. Viability was tested by Trypan blue exclusion and was always 85%.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that isolated hepatocytes can be safely preserved at 0 °C for at least 72 h without affecting their metabolic performance. More interesting was the observation of their functional efficiency upon reperfusion as assessed by functional tests both in vitro 22, 29–33 and in vivo 5, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The transfection vector was added to the hepatocyte suspension immediately after resuspension in UW solution, mixed by gentle inversion and left undisturbed at 0 °C for 24 or 48 h, respectively. Hepatocytes were then either transplanted into the spleens of recipient rats 23 or settled in culture 24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation